2020
DOI: 10.1186/s12888-020-02651-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Arabic version of the cardiac depression scale tested on Jordanian patients with cardiovascular diseases

Abstract: Background: The Cardiac Depression Scale (CDS) is an instrument to screen for depression, specifically in patients with cardiovascular diseases (CVD). The purpose of this study was to evaluate the psychometric properties of the Arabic version of the CDS in the Jordanian population. Method: A cross-sectional design was used for 304 participants diagnosed with CVD. An exploratory factor analysis (EFA) was performed to explore the underlying structure of the new Arabic version of the CDS tool. Results: Cronbach's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Therefore, the EFA of the Arabic-HESI was carried out using three factors, as suggested by the Kaiser method and scree plot. A maximum likelihood examination with a Promax rotation was used due to the probability of a correlation between the factors, with 0.30 set as the cut-off point for factor loading [ 53 ]. Thirty-three items were tested using the EFA analysis, and the item loadings were yielded, as shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the EFA of the Arabic-HESI was carried out using three factors, as suggested by the Kaiser method and scree plot. A maximum likelihood examination with a Promax rotation was used due to the probability of a correlation between the factors, with 0.30 set as the cut-off point for factor loading [ 53 ]. Thirty-three items were tested using the EFA analysis, and the item loadings were yielded, as shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The Cardiac Depression Scale (CDS), which is a 26-item self-rated questionnaire [ 24 ], was used to assess the levels of depression among the participants. The scale was developed by Hare and Davis in 1996 [ 24 ] and has been validated among the Jordanian population [ 3 ]. Responses are scored on a 7-point Likert scale, with higher scores indicating an increased number of depressive symptoms [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, it has been found that over 30% of patients with coronary artery disease (CAD) also manifest depressive symptoms [ 1 ]. Experts agree that depression is a major risk factor for CAD development and progression [ 2 , 3 , 4 , 5 , 6 ]. Conversely, people with heart disease are also at a greater risk of developing depression, according to the National Heart, Lung, and Blood Institute [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Cardiac Depression Scale (CDS), which is a 26-item self-rated questionnaire [21], was used to assess the levels of depression among the participants. The scale was developed by Hare and Davis in 1996 [21] and has been validated among the Jordanian population [3]. Responses are scored on a 7-point Likert scale, with higher scores indicating an increased number of depressive symptoms [21].…”
Section: Instrumentsmentioning
confidence: 99%
“…In fact, it has been found that over 30% of patients with coronary artery disease (CAD) also manifest depressive symptoms [1]. Experts agree that depression is a major risk factor for CAD development and progression [2,3,4,5,6]. Conversely, people with heart disease are also at a greater risk of developing depression, according to the National Heart, Lung, and Blood Institute [7].…”
Section: Introductionmentioning
confidence: 99%